Pre-Screening HIV-1 Reverse Transcriptase Resistance Mutations in Subtype B Patients Using a Novel Multiplex Primer Extension Assay - Jakobsen, Martin R.; Aggerholm, Anni; Jorgensen, Louise Bruun; Laursen, Alex; Ostergaard, Lars (Current HIV Research, 2009)
Antiretroviral therapy is standard treatment for HIV-infected patients. Such therapy has decreased mortality and morbidity, but treatment success is often jeopardized by the emergence of viral drug resistance. Moreover, in recent years there has been a reported rise in the incidence of transmitted drug resistance, highlighting the importance of pretreatment resistance screening. In this report, we describe the development and utility of a sensitive multiplex approach for detecting mutations conferring drug resistance to HIV-1 reverse transcriptase inhibitors. This protocol, termed HIVSNaPshot, utilizes a multiplex primer extension assay with capillary electrophoresis reporting altered nucleotides at nine important drug resistance mutation positions. Mutations were successfully detected to levels of 5% in viral quasispecies populations. Furthermore, although developed and optimised for HIV-1 subtype B, drug resistance mutations could also be detected in most non-B subtypes. Comparison of the HIV-SNaPshot with the commercial Viroseq genotyping system in 10 patients gave similar results, but importantly, additional resistance mutations were identified in several patients by the HIV-SNaPshot assay. Thus, the HIV-SNaPshot is a method capable to support standard genotyping for the determination of minority HIV-1 resistance mutations, with equivalent and perhaps greater sensitivity than Viroseq.
Keywords: Drug Resistance